Trait-Based Clustering and PCA Reveal Genetic Resources for Fodder MaizeImprovement (Plant Bulletin, 2025)
Maize is a versatile crop used for food, animal feed, fodder, and industrial purposes. Known for its high nutritional value and food safety for livestock. The genetic diversity of 50 maize genotypes was assessed based on eight morphological traits using RCBD design at NARC Islamabad during the spring season 2024.  The analysis of variance revealed significant variations for all recorded traits except number of cobs observed with non-significant variations(0.41ns). Hierarchical cluster analysis with complete linkage method grouped all genotypes into four clusters, indicating a broad genetic base. Cluster I comprises of maximum number of genotypes (22) indicated the genetic similarity among them, while Cluster IV observed with minimum number of genotypes (4).  In principal component analysis, the first four components had eigenvalues greater than 1, explaining 77.82% of the total variance. The identification of substantial genetic diversity in this study supports maize germplasm characterization, conservation, and future breeding improvements.
Keywords: Maize germplasm, fodder, cluster analysis, morphological traits and PCA